Nilai-nilai orang Bugis dalam Novel Antara Bumi dan Langit karya Syahriar Tato : Tinjauan sosiologi sastra - ADILUDDIN ([Yogyakarta] : Universitas Gadjah Mada, 2009)
This Research bent on be for analysis the works of novel entitles "Between Earth and sky" the works of Syahriar Tato. Research focus this is the moral values of people Bugis from within local literary work, namely novel "Between Earth and Sky". To analyse novel is referred, this research uses theory of art sociology, because relate to theory intended, in perspective that selected is art as the document of culture social that note fact of culture of social a society at one particular a period of certain. In perspective literary work as the document of culture social is literary work is not seen as an entire, but existing elementary body in literary work seen as a matter of get out of masterpiece unity. Thus, in perspective this only see direct relation between elementary body in a literary work and elementary body in society that depicted in literary work. As for method as used in research this is the method a literary sociology or this sociology art because method in accordance with theory as used in this research., that is theory of art sociology. Method Considerable study a literary sociology or sociology art starts from within literary work then connect it with literary work external world, or understanding in its operational is researcher starts from small structure in literary work, last develop it by fasten upon broader structure in society. This method is correct approach to study analysis about relation between art and social reality to finds and interpret fact of people life Bugis (Bugis society). From research result has been got and to description values of people moral Bugis from within novel "Between Earth and Sky". In other hand, this research also shows hit existence of relation or dependability between values of people moral Bugis from within novel referred, by culture value siri' also with main values culture that embraced or applied by people Bugis like value assitinajang (decency), value amaccang (intellectual), value alempureng (sincerity), value reso (hard work), and value agenengeng (firmness). Moral values, culture value sir?, and Bugis values culture superiority all it this, also base on view of people life Bugis. By it that, all valueses are referred, continued maintained and defended because shows function in has watched over in taking care of or maintain prestige and selfregard. Good to ownself or others.